The Dynamics of Remote Work Culture: How Psychological Well-Being and Digital Collaboration Tools Shape Employee Productivity - Bahtiar Maddatuang; Azura Zeyna Rohman; Aarav R. Menon (Vifada Management and Social Sciences, 2025)
This study explores how psychological well-being and digital collaboration tools interact to influence employee productivity within remote work environments. As remote and hybrid work models become increasingly normalized, organizations must understand the human–technology dynamics that drive sustainable performance. Using a quantitative approach with data from 462 remote employees across technology, education, and service sectors, this research applies structural equation modeling to examine direct and mediated relationships among work stress, digital overload, collaboration-tool usability, communication quality, and productivity outcomes. Findings reveal that psychological well-being significantly predicts productivity, with work engagement acting as a partial mediator. Digital collaboration tools also demonstrate a strong positive effect on productivity, particularly when usability, responsiveness, and synchronization are high. Furthermore, effective digital collaboration moderates the negative effects of stress and communication breakdowns. The study highlights the need for organizations to strategically manage digital ecosystems while supporting employee mental health to maximize performance in remote contexts.